QUALITY MANAGEMENT SYSTEM OF A PHARMACEUTICAL ORGANIZATION: CRITERIA AND IMPLEMENTATION - A. A. Klimenkova; L. N. Geller; A. A. Skripko; L. A. Gravchenko; N. V. Fedorenko (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
The aim of the study is a theoretical justification and development of a mechanism for the implementation of quality management systems (QMS) in the activities of retail trade in pharmaceutical products.Materials and methods. The study is based on the analysis of scientific literature data and Analytical Normative Documents regulating various aspects of QMS functioning in pharmaceutical organizations. Methods of documentary content analysis of international and national ISO standards, Series 9000, were used as the basis for the development and implementation of QMS organizations despite the type of their activities.Results. In the course of the study, the organization of the production process has been studied and the main production (business-) operations of seven structural subdivisions of "Apteka-Alex" LLC in Angarsk have been analyzed. The basic principles of QMS functioning are set forth and the author's methodology for its development for retail trade in pharmaceutical products has been presented, taking into account the specifics of the organizational structure and production activities of pharmacy organizations. The mechanisms and successive stages of the QMS implementation have been specified and given grounds for. In accordance with the requirements of GOST R ISO 9000:2015, the definitions and classification of the main production operations (business processes) of the studied pharmacies have been made up. In addition, the list of mandatory (core) and basic standard operating procedures (SOPs), detailing the main production (business-) processes, has been made up, and an algorithm for developing and testing SOPs has been outlined.Conclusion. The results of the study allowed us to justify and propose a step-by-step methods of QMS implementation into the work of pharmaceutical organizations in the retail sector. The first results of the approbation and use of the developed methodology show that it contributes to the rational construction and functioning of the QMS, in accordance with the requirements of the existing standards, as well as the optimization of administrative management of all production (business-) processes.